AsiaSim 2007 : Asia Simulation Conference 2007, Seoul, Korea, October 10-12, 2007 : proceedings - Park, Jin Woo (Springer, 2017)
This book is made up of selected papers from the Asia Simulation Conference 2007, held in Seoul, Korea, in October of 2007. The 42 revised full papers presented were carefully reviewed and selected from 120 submissions. After the conference, the papers went through another round of revision. The papers are organized in topical sections on a host of subjects. These include, among others, sections on numerical simulation, general application, and agent-based simulation.